Analysis of P4K Filling in The MCH Book with Factor of Maternal Death Based on Three Delays (3T) - Radicha, Salsha Billah Putri; Kusumawardani, Devi Arine; Miftakhurohmah, Sofiyanti (Jurnal Riset Kesehatan, 2023)
The Birth Preparedness and Complication Readiness Program (P4K) is an effort to overcome maternal mortality by reducing three delays (3T), late decision-making, late reaching health facilities, and late getting treatment. The purpose of this study was to analyze P4K filling in maternal and child health (MCH) books with the causes of maternal death based on three delays (3T). The method used in this study is quantitative and descriptive using data on 58 cases of maternal death found at the Jember District Health Office. The results of this study were that there were 15 (25.8%) cases of maternal death with P4K in the MCH handbook which were incompletely filled in and identified as experiencing three delays and 12 (20.6%) cases of maternal death with P4K in the MCH handbook which were not filled out. This research can be used as material for evaluating the Birth Preparedness and Complication Readiness Program (P4K). Â